Amnesty for whom? How the invisibles become essentials. - Della Rosa, Asia (PARTECIPAZIONE E CONFLITTO, 2021)
The article analyses the new law decree on regularisation introduced in Italy during the Covid-19 crisis, which subsumes human rights protections for sans papiers to the economic imperatives of labour market needs. The new law decree in fact seems to be in line with a more utilitarian logic, oriented towards the preservation of productive sectors at risk. Apparently, those who up until now have been invisible, neglected, and forgotten have suddenly become essential, at least in the numbers necessary to provide for the needs of the labour market. The work presented here examines the Italian context before, during and after the application of the amnesty, which saw the regularization of a limited number of migrants working in the agricultural sector. We intend to argue here that the regularization put into practice by the Italian government must be critically challenged, both in the premises and in the effects produced.